Synthesizing methylammonium-octhylammonium lead bromide hybrid perovskite nanoparticles - Liew, Josephine Ying Chyi; Baranoff, Etienne David; Rees, Thomas Wheildon; Abdi, Mahnaz M.; Talib, Zainal Abidin; Ahmad Kamarudin, Mazliana; Chen, Soo Kien; Muhammad, Farah Diana; Lee, Han Kee (2017)
Organic-Inorganic hybrid perovskite materials have attracted significant research interest in the field of photovoltaic as well as light emitting applications. Methylammonium-Octylammonium Lead Bromide (MOPbBr3) as one of the organic-inorganic hybrid perovskite materials have been synthesized through non template chemical precipitation technique. This technique is simple and allows low cost solution processing in low temperature route to form MOPbBr3 nanoparticles. The formation of MOPbBr3 nanoparticles has been characterized through X-ray Diffraction (XRD), Transmission Electron Microscopy (TEM), X-Ray Fluorences (XRF) analyzer and Nuclear Magnetic Resonance (NMR). Exploiting the optical properties through UV-Vis spectroscopy and photoluminescence spectroscopy specifically could greatly enhance the efficiency and functionality of applications based on this materials.